PENEGAKAN HUKUM TERHADAP PRAKTIK PERBUATAN â€œPAK OGAH â€œMENURUTUNDANG-UNDANG LALU LINTAS DAN ANGKUTAN JALAN DI KOTA PEKANBARU - Saragih, Kevin Jeremy Putra; R, Mukhlis; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Traffic congestion in Pekanbaru City is caused by the rapid population growth spike. Many of the people of Pekanbaru City come from other areas who are looking for a livelihood in Pekanbaru City. Because of this problem, there were young people known as â€œPak Ogahâ€ who did not have a permanent job and considered it an opportunity that could be exploited and made money in return for traffic control services. Some people think that Pak Ogah's actions are reluctant to disturb road users. Pak Ogah's actions are clearly not justified by law. Pak Ogah can be subject to fines and imprisonment. However, the existence of Pak ogah is difficult to eliminate, not only because law enforcement is still weak, but also due to community participation to prevent illegal levies which are still minimal. The formulation of the problem summarized in this study is how the implementation of law enforcement, obstacles, and efforts in overcoming the practice of Pak Ogah's activities in Pekanbaru City. The purpose of this research is to find out the implementation of law enforcement against Pak Ogah, to know the obstacles in enforcing Pak Ogah's practices, and to find out the efforts made to overcome obstacles in law enforcement of Pak Ogah's practical activities.The method used in this research is sociological research. The data collection technique used by the author is through interviews, questionnaires, and literature studies. The author analyzes the data using a qualitative method, namely by collecting data from observations and interviews with several respondents.The results of the research conducted, namely, the implementation of law enforcement on the practices carried out by Mr. Ogah in the city of Pekanbaru is still not in accordance with the provisions stipulated in Law No. 22 of 2009 concerning Road Traffic and Transportation, the obstacles experienced in carrying out enforcement The law is a large number of Mr. Ogahs, having a thug background, and Mr. Ogah does not understand the law itself. Therefore, according to the author, it is very necessary to carry out socialization and guidance about the law from an early age.Keywords: Mr. Ogah, Traffic, socialization